Case report: Wernicke–Korsakoff syndrome after bariatric surgery - Bento, Margarida Alves; Vieira, João Barriga; Silva, Maria Leonor; Camolas, José (Frontiers in Nutrition, 2024)
Vitamin and mineral deficiencies are prevalent nutritional disorders following bariatric surgery. Although they are more prevalent after malabsorptive procedures such as bypass, they also occur in restrictive procedures such as gastric sleeve. The mechanisms that lead to the occurrence of these deficits are related to the presence of poor nutritional intake or poor adherence to multivitamin and multimineral supplementation. Wernicke-Korsakoff syndrome (WKS) is an acute neurological disorder resulting from thiamine deficiency. This syndrome is composed of two distinct phases: first, Wernicke Encephalopathy (WE), the acute phase of this syndrome, which is characterized by a triad of mental confusion, ocular signs, and ataxia, followed by the chronic phase of WKS, called Korsakoff's Syndrome (KS) which is known for the presence of anterograde amnesia and confabulation. We aim to report a case of a patient with WKS after bariatric surgery. Patient's retrospective chart review was done in order to retrieve the relevant clinical data. The patient was a 24years-old, female, with a BMI of 48kg/m 2 that was submitted to a sleeve gastrectomy surgery for morbid obesity. Over the following 2 months, recovery from surgery was complicated by non-specific symptoms such as nausea, recurrent vomiting and a significant reduction in food intake, which led the patient to visit the emergency department six times with hospitalization on the last occasion for a definitive diagnosis. During the fifteen days of hospitalization, the patient developed ocular diplopia, nystagmus, complaints of rotatory vertigo and gait abnormalities. A magnetic resonance imaging of the head was performed but revealed no significant changes. After a formal neurological assessment, treatment with parenteral thiamine (100 mg, 3 times a day) was started, without prior dosing. The clinical improvement observed confirmed the diagnosis of WKS. Bariatric surgery may contribute to thiamine deficiency and, consequently, to WKS. Education about the adverse consequences of